Contamination of pharmaceutical products by the Burkholderia cepacia complex and its possible impacts on healthcare and industry: A bibliographic review (Research, Society and Development, 2024)
The Burkholderia cepacia complex (BcC) is a group of bacteria of the genus Burkholderia known to cause opportunistic infections, being able to acquire resistance to antibiotics and antiseptics. Despite this, it is a group of bacteria that is disguised in the pharmaceutical environment and its potential risk as a contaminating agent is still disregarded, since the Brazilian pharmacopeial methods that establish the microbiological limits for pharmaceutical products do not include them. Therefore, the objective of this article was to carry out a bibliographic review on cases of contamination of pharmaceutical products (of common and hospital use) by the BcC around the world and discuss the possible health and economic impacts based on data obtained through searches in PubMed, VHL, Scielo and Scopus databases. Thus, it is suggested that for the circulation of these drugs it is necessary to update pharmacopeial methods (mainly for analysis of water and finished product) including the BcC complex.